1989
DOI: 10.1073/pnas.86.1.197
|View full text |Cite
|
Sign up to set email alerts
|

At least two mutant alleles of ornithine delta-aminotransferase cause gyrate atrophy of the choroid and retina in Finns.

Abstract: Gyrate atrophy of the choroid and retina (GA) is an inherited chorioretinal degeneration caused by deficiency of ornithine 8-aminotransferase (OAT; L-ornithine: 2-oxo-acid aminotransferase; EC 2.6.1.13). GA is one of the "Finnish genetic diseases," a group of several rare monogenic disorders that occur with increased frequency in the Finnish population. Using a combination of RNase A protection, genomic cloning, and polymerase chain reaction amplification of genomic DNA, we found one of two missense mutant OAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Gyrate atrophy of the choroid and retina caused by deficiency of ornithine 3-aminotransferase (EC 2.6.13) is one such Finnish genetic disease. Surprisingly, at least two different mutant alleles of ornithine 8-aminotransferase have been found in the Finnish population (21). In this study, we have shown that in eight Finnish aspartylglycosaminuria patients from different pedigrees two separate point mutations are found close to the carboxylterminal end of the heavy chain of glycoasparaginase.…”
Section: T I G M Vvi H K T G H I a A G T S T N G I K F K I H G R V G mentioning
confidence: 71%
“…Gyrate atrophy of the choroid and retina caused by deficiency of ornithine 3-aminotransferase (EC 2.6.13) is one such Finnish genetic disease. Surprisingly, at least two different mutant alleles of ornithine 8-aminotransferase have been found in the Finnish population (21). In this study, we have shown that in eight Finnish aspartylglycosaminuria patients from different pedigrees two separate point mutations are found close to the carboxylterminal end of the heavy chain of glycoasparaginase.…”
Section: T I G M Vvi H K T G H I a A G T S T N G I K F K I H G R V G mentioning
confidence: 71%
“…R13516) from the National Genome Center, Lawrence Livermore National Laboratory (Livermore, CA) and sequenced the cDNA insert. Using this putative P5CS EST clone as a probe, we screened Ͼ5 ϫ 10 5 plaques from both the human kidney and small intestine cDNA library as described (30,31). We purified two positive plaques, one (HsP5CS.K5) from kidney cDNA library and the other (HsP5CS.G1) from the small intestine cDNA library, through two additional cycles of screening, subcloned the inserts (HsP5CS.K5, 2.7 kb; HsP5CS.G1, 2.8 kb) into pBluescript II KS(ϩ), and sequenced them.…”
Section: Methodsmentioning
confidence: 99%
“…The mutations were selected as targets because they occur with a high frequency in the Finnish population and populationbased screening for them would be clinically relevant. Five of the mutations cause severe recessive disorders [infantile neuronal ceroid lipofuscinosis (INCL; Vesa et al 1995), aspartylglucosaminuria (AGU; Ikonen et al 1991), gyrate atrophy (GA; Mitchell et al 1989) and nonketotic hyperglycinemia (NKH; Kure et al 1992)] belonging to the ''Finnish disease heritage,'' (for review, see Peltonen et al 1995) and occur with a combined population frequency of carriers of ∼0.05. Three mutations in the low-density lipoprotein receptor (LDLR) gene (Aalto-Setälä et al 1989;Koivisto et al 1991Koivisto et al , 1995 that cause familial hypercholesterolemia (FH) with the estimated prevalence of 1 in 500, both in Finland and worldwide, were also included in the panel.…”
mentioning
confidence: 99%